Transformation of insurance from the aspect of the development of autonomous vehicles - Vojvodić-Miljković Nevenka; Mandić Dejan; Miloradović Milica (Trendovi u Poslovanju)
Vehicle manufacturers are making great strides in developing self-driving cars that don't harm the climate. The goal of everyone, be they large industrial companies or startups, is to reach vehicles that will be self-driving and emit no harmful gases as soon as possible through innovative technologies and the development of telecommunications. The share of vehicles in sales is increasing year by year. The proclaimed goals are expected to be achieved in the largest number of developed countries. Self-driving vehicles offer great potential to improve road efficiency, reduce traffic accidents, increase productivity, and minimise our environmental impact. Looking ahead, electric vehicles are increasingly on the roads, while driverless cars and delivery drones are seemingly poised for more widespread adoption in the future. Autonomous vehicles are likely to be the next stage in the continued transformation of motor insurance. Therefore, the authors consider this topic to be relevant both from the economic and legal aspects.